Environmental impact of oil palm processing on some properties of the on-site soil in a growing city in Nigeria - TO, Ogunbode; O, Aliku; PO, Ogungbile; Olatubi, IV; VA, Adeniyi; EA, Akintunde (Frontiers in Environmental Science, 2022)
Both natural and anthropogenic activities exert great influence on soil conditions, with some being beneficial to its health. This study was conducted to assess the impact of oil palm processing activities on selected soil properties in Iwo, Nigeria. Soil samples taken from upstream, mid-section and downstream points along an oil palm mill dumpsite were compared against a control. Soil organic matter, bulk density, and soil moisture were determined using standard procedures, while soil structural stability was estimated using stability index. Soil organic matter was significantly higher at the oil palm mill relative to the control, and reduced by 50.8% and 64.4% at the upstream and downstream relative to the mid-section. Bulk density did not differ significantly among the sampling points, but increased at the upstream, mid-section and downstream by 2.4% – 13.1% compared with the control. Soil moisture at field capacity was substantially higher at the site relative to the control, with the upstream having the highest value (0.94 m3 m-3). Soil structural stability was superior at the mid-section, and reduced by 57.0% – 76.2% at the upstream, downstream and control points, respectively. In general, oil palm mill processing activities improved the on-site soil organic matter and its physical conditions.